2003
DOI: 10.1124/jpet.102.038018
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawal from Repeated Cocaine Alters Dopamine Transporter Protein Turnover in the Rat Striatum

Abstract: Several studies have shown that repeated cocaine administration, followed by withdrawal, alters dopamine transporter (DAT) levels in the rat. These changes must arise from changes in either transporter protein production or degradation, or both. Previously, our laboratory developed an approach to measure the synthesis rate, degradation rate constant, and half-life of DAT in the rat striatum and nucleus accumbens after administration of the irreversible dopamine transporter ligand, RTI-76. These initial studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…2002). With chronic cocaine treatment, most evidence points to a decrease in DAT expression following a sufficient withdrawal period (Kuhar and Pilotte 1996), although both decreased and increased mRNA/protein levels have been reported (for a recent review of the literature see Kimmel et al . 2003).…”
Section: Cocainementioning
confidence: 99%
“…2002). With chronic cocaine treatment, most evidence points to a decrease in DAT expression following a sufficient withdrawal period (Kuhar and Pilotte 1996), although both decreased and increased mRNA/protein levels have been reported (for a recent review of the literature see Kimmel et al . 2003).…”
Section: Cocainementioning
confidence: 99%
“…Turnover measurements reflect release and/or synthesis rates that have been found to change and reflect activity even when levels do not. Similarly, protein levels may not change while changes in turnover rates are significant (for example, Kimmel et al, 2003). However, methods for measuring turnover rates of most peptides have not been developed.…”
Section: Discussionmentioning
confidence: 99%
“…It is assumed that the rate of return of binding reflects new synthesis, rather than the chemical separation and loss of RTI-76 blockade. Studies by Kimmel, et al, [10, 11] have shown (Table 1), that acute cocaine administration can cause a significant increase in the half-life of DATs, while the change in Bmax (or level) of the transporters is not significantly different. Similarly, withdrawal from repeated cocaine results in a significant decrease in half-life, while again there is no change in the Bmax or levels of DATS in treated animals versus control animals.…”
Section: Applications and Examplesmentioning
confidence: 99%